Inhibition of NF-κB transcriptional activation in HepG2 cells by diterpenoids from the soft coral Sinularia maxima - Thao, Nguyen Phuong (Pharmaceutical Society of Korea, 2013)
Anti-inflammatory transcriptional effects of nineteen compounds (1–19) from the soft coral Sinularia maxima were evaluated using NF-κB luciferase and reverse transcriptase polymerase chain reaction. Compounds 1, 2, 4, 8, 15, 17, and 18 significantly inhibited TNFα-induced NF-κB transcriptional activity in HepG2 cells in a dose-dependent manner, with IC(50) values ranging from 15.81 ± 2.29 to 29.10 ± 1.54 μM. Furthermore, the transcriptional inhibitory function of these compounds was confirmed by a decrease in intercellular adhesion molecule-1 and inducible nitric oxide synthase gene expression levels in HepG2 cells. These results provide a scientific rationale for the use of the soft coral S. maxima warrant further studies to develop new agents for the prevention and treatment of inflammatory.